2003
DOI: 10.1099/mic.0.26562-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the LlaCI methyltransferase from Lactococcus lactis subsp. cremoris W15 provides new insights into the biology of type II restriction–modification systems

Abstract: The gene encoding the LlaCI methyltransferase (M.LlaCI) from Lactococcus lactis subsp. cremoris W15 was overexpressed in Escherichia coli. The enzyme was purified to apparent homogeneity using three consecutive steps of chromatography on phosphocellulose, blue-agarose and Superose 12HR, yielding a protein of M r 31 300±1000 under denaturing conditions. The exact position of the start codon AUG was determined by protein microsequencing. This enzyme recognizes the specific palindromic sequence 59-AAGCTT-39. Puri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 83 publications
(64 reference statements)
1
18
0
Order By: Relevance
“…The plasmid complement of L. lactis DPC3758 harbors a significant array of defense mechanisms against phage attack, including 1 type I R/M and 2 type II R/M systems, which confirms suggestions that the latter mechanisms are the most common in lactococci (Mruk et al, 2003). Type I R/M systems are typically made up of 3 genes (hsdRMS), transcribed in the same direction, and coding for 3 subunits that are responsible for DNA restriction (HsdR), modification (HsdM), and specificity (HsdS), respectively (Murray, 2000).…”
Section: A Battery Of 3 R/m Systems Protects L Lactis Dpc3758 Againssupporting
confidence: 74%
“…The plasmid complement of L. lactis DPC3758 harbors a significant array of defense mechanisms against phage attack, including 1 type I R/M and 2 type II R/M systems, which confirms suggestions that the latter mechanisms are the most common in lactococci (Mruk et al, 2003). Type I R/M systems are typically made up of 3 genes (hsdRMS), transcribed in the same direction, and coding for 3 subunits that are responsible for DNA restriction (HsdR), modification (HsdM), and specificity (HsdS), respectively (Murray, 2000).…”
Section: A Battery Of 3 R/m Systems Protects L Lactis Dpc3758 Againssupporting
confidence: 74%
“…Zn 2ϩ acted as a strong inhibitor of M.PabI-catalyzed methylation, in contrast to Mg 2ϩ , Ca 2ϩ , and Mn 2ϩ , all of which showed no significant inhibition. It has been reported that the methylation activities of M.HindIII, M.LlaCl, and M.EcoVIII were inhibited by Zn 2ϩ (35). An inhibitory effect of Mg 2ϩ was also observed with these enzymes.…”
Section: Effect Of Cationsmentioning
confidence: 84%
“…The presence of metal ions is not an absolute requirement for M.BcgI [29], M.AloI [30], M.Eco57I [31], and M.MmeI [32] but the methylation activity of these enzymes was enhanced in the presence of Mg 2+ . On the other hand, M.HindIII, M.LlaCI, M.EcoVIII [33], M.PabI [18], M1.MboI, M2.MboII, M1.NcuI, M.NcuII [34, 35], and M.FokI [36] showed inhibition of methylation activity in the presence of various metal ions. It is clear that the activities of DNA MTases characterized so far respond differently in the presence of metal ions.…”
Section: Resultsmentioning
confidence: 99%